USING ONOMATOPOEIA IN COMIC TO IMPROVE VOCABULARY - Eliza, Tiara; Sari, Desi Ratna; Irawati, Menik (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2024)
In the field of second language teaching, vocabulary has been one of the most neglected areas in the classroom. That is why there are many students who lacks of vocabulary will find difficulties in language learning process. They will find difficulties in communication. Therefore vocabulary has an important role in communication process both spoken and written. Vocabulary is needed to support a success communication. This study was meant to find out how to improve vocabulary by using onomatopoeic expression in comic and to describe some challenges in using comic as a media of teaching and learning process. This study used a qualitative descriptive analysis. The participants were taken from the students in private classes. The research data is collected by using test (test after the first treatment and test after the second treatment) and by observation for collecting data on the students’ motivation in improving vocabulary mastery using onomatopoeic expression. The data were analyzed by using the descriptive analysis. The result showed that in the first cycle, the students’ average was 65.8, then, on the second treatment, the students’ average increase to be 75.9. It can conclude that teaching vocabulary by using onomatopoeic expression in comic can be used as media to improve students’ vocabulary ability.